Operations on Arc Diagrams and Degenerations for Invariant Subspaces of Linear Operators - Kosakowska, Justyna; Schmidmeier, Markus (arXiv.org, 2013)
We study geometric properties of varieties associated with invariant subspaces of nilpotent operators. There are reductive algebraic groups acting on these varieties. We give dimensions of orbits of these actions. Moreover, a combinatorial characterization of the partial order given by degenerations is described.